2016
DOI: 10.1111/tid.12591
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a cytomegalovirus serology dual‐testing strategy in hematopoietic stem cell transplant recipients

Abstract: CMV-seronegative hematopoietic stem cell transplant recipients may be misclassified as seropositive if testing is performed after receipt of blood products or when using assays optimized for sensitivity at the expense of specificity. This misclassification may negatively affect post-HSCT outcomes for individual patients and studies that rely on accurate CMV serology reporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…However, it is worth noting that in polytransfused patients (as exemplified by many haematological patients awaiting an allogeneic transplant), the serological status may be an artefact of a passive immunization mechanism. Discrepancies in CMV have been observed in up to 29%-33% of patients when this has been analysed ( 86 , 87 ). Routinely determined serostatus is still currently used as a criterion for estimating CMV reactivation risk before transplant.…”
Section: In the Haematological Settingmentioning
confidence: 99%
“…However, it is worth noting that in polytransfused patients (as exemplified by many haematological patients awaiting an allogeneic transplant), the serological status may be an artefact of a passive immunization mechanism. Discrepancies in CMV have been observed in up to 29%-33% of patients when this has been analysed ( 86 , 87 ). Routinely determined serostatus is still currently used as a criterion for estimating CMV reactivation risk before transplant.…”
Section: In the Haematological Settingmentioning
confidence: 99%
“…In any case, the accurate determination of D/R CMV serostatus prior to allo‐HSCT is of major relevance. In a recent study, Perry and Hakki noted that allo‐HSCT recipients may be miscategorized as being CMV seropositive if serological testing is performed after receipt of blood transfusions or when employing assays with suboptimal specificity . Recently, Loeth et al found CD4 + and/or CD8 + pp65‐specific T‐cell responses in five out of 44 seronegative individuals.…”
Section: Introductionmentioning
confidence: 99%